Online Algorithms for Location-Aware Task Offloading in Two-Tiered Mobile Cloud Environments - Qiufen Xia; Weifa Liang; Zichuan Xu; Bingbing Zhou (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
Mobile Cloud Computing (MCC) is emerging as a main ubiquitous computing platform which enables to leverage the resource limitations of mobile devices and wireless networks by offloading data-intensive computation tasks from resource-poor mobile devices to resource-rich clouds. In this paper, we consider an online location-aware offloading problem in a two-tiered mobile cloud computing environment consisting of a local cloudlet and remote clouds, with an objective to fair share the use of the cloudlet by consuming the same proportional of their mobile device energy, while keeping their individual SLA, for which we devise an efficient online algorithm. We also conduct experiments by simulations to evaluate the performance of the proposed algorithm. Experimental results demonstrate that the proposed algorithm is promising and outperforms other heuristics.